An exploratory study using framework analysis to investigate health‐seeking behaviour in patients with psoriasis. (12th May 2017) - Simpson, J.K.; Wilson, M.; Ahmed, A.A.; Mizara, A.; Clarke, A.; McBride, S.R.
Summary: Background: Psoriasis is a long‐term inflammatory skin disorder, with negative effects on employment, relationships and social function, frequently causing reduced quality of life. People with psoriasis often present to secondary care late into their condition but the reasons for this are unknown. Objectives: To examine the patient pathway, health‐seeking behaviour and drivers for referral to secondary care in patients with psoriasis. Methods: Sixteen patients with mild‐to‐severe psoriasis, newly referred to secondary care participated in a semi‐structured interview. Scripts were analysed by a thematic framework. Results: The median duration of time living with psoriasis was 15 years at referral. Drivers of secondary care referral included rapid deterioration or extremis, development of comorbidities, knowledge of treatment options, and influence of partners and friends. Reasons for late presentation to secondary care include familial experience of psoriasis, lack of follow‐up after the initiation of treatments, beliefs that psoriasis is incurable and must be tolerated, and that psoriasis is not life threatening and therefore not worthy of medical help and difficulty in obtaining a secondary care referral. A common pathway from seeking help at psoriasis onset, evolving into the development of delayed health seeking later in the pathway, was identified. Conclusions: Identifying the causes of delay in presentation to secondary care and effective treatment ascertains key areas to target. Health seeking early in the disease pathway provides a 'window of opportunity' for intervention, which may enable people with psoriasis to obtain early, effective treatment and achieve their full life potential. Abstract : What is already known about this topic? Psoriasis negatively impacts on employment prospects, relationships, psychological well‐being and social functioning, which may lead to reduced quality of life. People with psoriasis often delay seeking help. What does this study add? Drivers of secondary care referral include rapid deterioration, development of comorbidities, knowledge of treatment options and influence of partners and friends. Reasons for late presentation include familial experience of psoriasis, lack of assessment following initiation of treatment, development of views that psoriasis is incurable and must be tolerated, and that psoriasis is not life threatening and not worthy of medical help. Identifies a common pathway with an early 'window of opportunity' to intervene. What are the clinical implications of this work? Earlier effective treatment may reduce the impact of psoriasis and enable patients to achieve their full life potential. This may guide policy and decision making in those who care for patients with psoriasis. Respond to this article Linked Comment:  Cowdell. Br J Dermatol 2017; 177 :615–616